2010
DOI: 10.1111/j.1750-3841.2010.01800.x
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic Responses to Sweetened Dried and Raw Cranberries in Humans with Type 2 Diabetes

Abstract: This study assessed the metabolic response to sweetened dried cranberries (SDC), raw cranberries (RC), and white bread (WB) in humans with type 2 diabetes. Development of palatable cranberry preparations associated with lower glycemic responses may be useful for improving fruit consumption and glycemic control among those with diabetes. In this trial, type 2 diabetics (n= 13) received WB (57 g, 160 cal, 1 g fiber), RC (55 g, 21 cal, 1 g fiber), SDC (40 g, 138 cal, 2.1 g fiber), and SDC containing less sugar (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 25 publications
2
43
0
1
Order By: Relevance
“…Polydextrose can influence the effect of sugar on the body in two ways. For instance, the consumption of dried cranberries with less sugar and 10 g added polydextrose led to lower increases in both blood glucose and insulin compared to dried cranberries with added sugar in subjects with Type 2 DM [103]. Similar observations have been made with overweight subjects [104].…”
Section: Dietary Fiberssupporting
confidence: 55%
“…Polydextrose can influence the effect of sugar on the body in two ways. For instance, the consumption of dried cranberries with less sugar and 10 g added polydextrose led to lower increases in both blood glucose and insulin compared to dried cranberries with added sugar in subjects with Type 2 DM [103]. Similar observations have been made with overweight subjects [104].…”
Section: Dietary Fiberssupporting
confidence: 55%
“…The impact of strawberry fruits on inhibition of glucose uptake, transportation, normalizing blood glucose levels and carbohydrate digestive enzymes inhibition have been demonstrated in mechanistic studies [27,28,29]. Results from Wilson et al [30] and DeFuria et al [31] postprandial researches might provide more evidence for the latter metabolic mechanisms. Though results from studies which had investigated the effects of FDS on metabolic features of obese, hyperlipidemic subjects or subjects with metabolic syndrome revealed no significant changes in serum glucose concentration [19,20,21,22,23].…”
Section: Discussionmentioning
confidence: 90%
“…In volunteers with type 2 diabetes, cranberries with 10g of polydextrose showed attenuated plasma glucose and insulin response compared to cranberries with glucose [127]. In one study with healthy adults, significantly lower postprandial glucose levels were observed after ingestion of strawberry jam with 40 % polydextrose than after ingestion of strawberry jam sweetened with sugar, corn syrup, or apple juice, but this study did not measure insulin [128].…”
Section: Polydextrose Effect On Glycemic Control and Insulin Responsementioning
confidence: 97%
“…In some of these studies the response is observed because polydextrose was used as sugar substitute to lower the caloric content of the snack/product [127,128]. In [127] the beneficial insulin reduction was observed not to be in 1:1 ratio with caloric reduction so there might be additional beneficial effect apart from lowering the overall calorie content.…”
Section: Polydextrose Effect On Glycemic Control and Insulin Responsementioning
confidence: 99%